Fenomena Kecanduan Game Online Pada Remaja (Studi Kasus di Kec. Sukaraja, Kab. Seluma, Prov. Bengkulu) - Sri Wahyu Nurhidayati; Moch. Iqbal (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to describe and analyze the phenomenon of online game addiction in teenagers in Sukaraja District, and the factors that cause the phenomenon of online game addiction in teenagers in Sukaraja District, what is the impact of the phenomenon of teenagers being addicted to online games in the District. The type of research used in this research is descriptive qualitative. The research results showed that the phenomenon of teenagers addicted to online games in Sukaraja District is a normal thing for teenagers who are involved in the world of online games. On average, those who are addicted to online games are school age children, starting from middle school, high school and college students, almost all of whom have experienced playing online games. Many things influence and cause this phenomenon to occur, starting from the teenagers themselves, parents or family, environmental factors, as well as the learning process followed by teenagers at school and also the influence of peer interactions. The impact of online game addiction has an impact on aspects of teenagers' lives which include health, psychological, academic, social and financial aspects.